Pengaruh Penerapan Teknik Behavior Contract Terhadap Kedisiplinan Siswa Kelas 1 di SDN 3 Balak Kabupaten Banyuwangi - Peni Lestari, Maulita; Weyara Dienda Saputri, Senny; Syarifatul Umami, Yuniarta (Nak-Kanak: Journal of Child Research, 2024)
Discipline is the behavior of obeying or complying with rules based on the encouragement and awareness that arises within oneself. There are several behaviors that lack discipline in the school environment, namely students arriving late to school, not paying attention to the teacher during learning, not doing assignments and often leaving the classroom during learning. One effort that teachers can make is modifying student behavior using the behavior contract technique. So, this research aims to determine whether there is an influence of the behavior contract technique on the discipline of grade 1 students at SDN 3 Balak, Banyuwangi Regency. The research method uses pre-experimental with a one shot case study model using t test analysis for related samples. This research design uses one group of 16 students, the sample collection method uses a total sampling technique. The population in this study were grade 1 students at SDN 3 Balak, Banyuwangi Regency. The results of the t test analysis for related samples showed a result of 2,131 < 3,964, which means there is a difference in the degrees of freedom in the disciplinary behavior of students who were treated using the behavior contract technique and students who were not treated using the behavior contract technique. The value of the significance of the sample t test is 0,001 < 0,05. So it can be concluded that there is an influence of the application of behavior contract techniques on the discipline of grade 1 students at SDN 3 Balak, Banyuwangi Regency.